Threats to Contemporary Economic Order - Klisiński, Janusz (Political Preferences, 2020)
The biggest threats to contemporary economic order were chronologically the bipolarity of the world after 1945, in which one of the poles despised money and the other based its prosperity on money. An attempt to create a unipolar world already dominated by the US dollar, practically was hardly acceptable. The US showed its strength when Japan in 1995 became a pretender to be No. 1 in the global economy. Also in 2008, American banks triggered a global financial crisis by creating bubbles of toxic real estate loans. The 2008 financial crisis also started a crisis of liberal democracy. China was much more powerful than Japan as the next pretender to become No. 1 in the global economy. About it can be seen as the beginning of a global conflict between the United States and China. In addition, the coronavirus pandemic has stopped globalization and is causing a global crisis.